(untitled) (Research, Society and Development, 2022)
Introduction: Patients with transverse maxillary deficiency may have unilateral or bilateral posterior crossbite, crowded and rotated teeth and narrow palate. The treatment for adults is surgically assisted rapid maxillary expansion, a procedure that results in changes not only to bones, but also to teeth, nasal cavity, air space, lips and surrounding soft tissues. Objective: This study evaluated dentoskeletal changes in patients that underwent surgically assisted rapid maxillary expansion (SARME). Methods: Cone beam computed tomography (CBCT) scans were obtained before and after SARME. The thickness of buccal and lingual cortical bone and the angle of the long axis of posterior maxillary teeth were measured. Data were analyzed statistically. Results showed changes in thickness of buccal and lingual cortical bone and tooth movement and tipping. Conclusion: Tooth tipping increased and buccal bone thickness decreased, although osteotomies were used.